Do individuals higher in impulsivity drink more impulsively? A pilot study within a high risk sample of young adults. (February 2017) - Stevens, Angela K.; Littlefield, Andrew K.; Talley, Amelia E.; Brown, Jennifer L.
Abstract: Extant literature has established a strong relation between individual differences in "impulsivity" and alcohol consumption. However, the relation between "impulsivity, " intentions-to-drink, and alcohol consumption has remained understudied. As a part of a larger study, 77 participants (60.5% female, 76.3% White, M age = 20.8) completed 10 days of daily diary reports regarding their intention to use alcohol and alcohol consumption. Hierarchical linear modeling (HLM) was used to estimate within-person relations between intentions-to-drink and subsequent alcohol use. All models were adjusted for participant age, biological sex, and day of the week. Results showed a strong positive association between daily intention to consume alcohol and self-reported alcohol use ( β = 0.50, p < 0.01). Importantly, tests of interactions indicated that individuals higher in impulsivity were not significantly more likely to engage in unplanned drinking. Multilevel mediation analyses indicated significant indirect effects between impulsivity-like constructs, including positive urgency, lack-of-planning, and self-report delay discounting, and reported daily alcohol consumption via higher overall (i.e., between-person) levels of intentions-to-drink; that is, individuals who reported higher levels of these impulsivity-related constructs were more likely to intend to drink across the 10-days and, in turn, consumed more alcohol. Findings from the study suggest that treatment providers could address drinking intentions among individuals higher in impulsivity and work to establish potential replacement behaviors to reduce alcohol consumption in this population. Highlights: This study examined the mechanisms of the impulsivity-intention relation for alcohol. This study utilized a daily diary design with advanced statistical analyses. Facets of impulsivity had an indirect effect on alcohol use through intentions to drink. Impulsive individuals did not engage in unplanned drinking as hypothesized.